Параметры кольцевых резонаторов на Н- и крестообразных волноводах, изогнутых в плоскости Е - Зоркин, А.Ф.; Терещенко, А.И. (Radiotekhnika, 1966)
Параметры кольцевых резонаторов на Н- и крестообразных волноводах, изогнутых в плоскости Е